STUDI KOMPARASI HASIL BELAJAR MATEMATIKA ANTARA SISWA LAKI-LAKI DAN PEREMPUAN KELAS V SD NEGERI 35 PEKANBARU - Hermawan, Geofany; Syahrilfuddin, Syahrilfuddin; Zufriady, Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The background of this research is the comparison of learning outcomes between male and female students in the fifth grade of elementary school mathematics. The purpose of this study was to determine how the mathematics learning outcomes between male and female students and to find out whether there was a significant difference in mathematics learning outcomes between male and female students in fifth grade elementary school. This research is a comparative study with a quantitative approach. The population in this study were fifth grade students at SD Negeri 35 Pekanbaru. The sampling technique used a saturated sample for men with a total of 20 people for women 20 people with a total sample of 40 students. The data collection used is in the form of tests that have been done by students. The data obtained were analyzed using descriptive and inferential statistics with statistical techniques t (t test). The results of the descriptive research show that the average score of male students is 77.50 while the average score of female students is 82.75. The results of hypothesis testing using t-test obtained the value of Sig(2-tailed) > or ( 0.316 > 005 ). This shows that H0 is accepted and H1 is rejected, so there is no significant difference in mathematics learning outcomes between male and female students in fifth grade at SD Negeri 35 Pekanbaru.Key Words: Learning Outcomes, Mathematich, Gender